Different actions of intracellular zinc transporters ZIP7 and ZIP13 are essential for dermal development - Lee, Mi Gi; Bin, Bum Ho (International Journal of Molecular Sciences, 2019)
Two mesenchymal zinc transporters, ZIP7 and ZIP13, play critical roles in dermal development. ZIP7 and ZIP13 are the closest among the conserved mammalian zinc transporters. However, whether their functions are complementary remains a controversial issue. In the present study, we found that the expression of ZIP13, but not ZIP7, is elevated by transforming growth factor beta (TGF-β) treatment, indicating that TGF-β-mediated ZIP13 amplification is crucial for collagen production during dermal development. Genome-wide gene expression analysis revealed that ~26% of genes are dependent on either ZIP7 or ZIP13, which is greater than the ~17% of genes dependent on both of them. ZIP7 depletion induces endoplasmic reticulum (ER) stress in mesenchymal stem cells, resulting in significant inhibition of fibrogenic differentiation. However, ZIP13 depletion does not induce ER stress. Though both ZIP7 and ZIP13 contain traditional ER signal peptides for their intracellular localization, their distributions are distinct. When ZIP7 and ZIP13 are coexpressed, their localizations are distinct; ZIP7 is located on the ER, but ZIP13 is located on both the ER and Golgi, indicating that only ZIP13 is a zinc gatekeeper on the Golgi. Our data illustrate that the different actions of ZIP7 and ZIP13 are crucial for dermal development.
Keywords: Animals; Cation Transport Proteins; Dermis; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Genome; Genome-Wide Association Study; Mesenchymal Stem Cells; Mice; Mice, Knockout; Models, Biological; Organogenesis; Zinc; Browning; Connective tissue; Mesenchymal stem cells; Zinc; ZIP13; ZIP7